The effect of an ecological imagery program on soccer performance of elite players - Seif-Barghi, T.; Kordi, R.; Memari, A.-H.; Mansournia, M.-A.; Jalali-Ghomi, M. (Asian Journal of Sports Medicine, 2012)
Purpose: Despite the acknowledged impact of imagery on performance, ecologically sound studies investigating imagery and its effects on performance subcomponents in real games are surprisingly limited. The aim of this study was to investigate the effects of imagery training on passing improvement in elite soccer players.